Lowest Instrumented Vertebra Selection in Posterior Cervical Fusion: Does Cervicothoracic Junction Lowest Instrumented Vertebra Predict Mechanical Failure?. Issue 8 (15th April 2021) - Labrum, Joseph T.; Khan, Inamullah; Archer, Kristin R.; Abtahi, Amir M.; Stephens, Byron F.
Abstract : Study Design: Retrospective. Objective: The purpose of this study is to evaluate the effect of posterior cervical fusion lowest instrumented vertebra (PCF LIV) selection on incidence of mechanical failure, revision surgery, and patient-reported outcomes (PROs). Summary of Background Data: Recent studies indicate that the LIV in PCF may contribute to the risk of mechanical failure. To date, the evidence available to guide spine surgeons in the selection of PCF LIV remains limited. Methods: All patients undergoing PCF at a single institution were prospectively entered into a spine registry which was retrospectively queried. Data collection included demographics, pathology, operative variables, construct LIV, outcomes of mechanical failure, revision surgery, and patient-reported disability, pain, and quality of life. Results: Of 438 patients undergoing PCF from 2006 to 2019, 106 patients had an LIV of C7, T1, or T2, a minimum of 1-year follow-up, and met all study inclusion criteria. LIV cohorts were C7 LIV (36), T1 LIV (42), and T2 LIV (28). There were no between-group differences in patient demographics, operative variables, or postoperative follow-up across the three LIV cohorts. Mechanical failure rates for C7, T1, and T2 LIV were 30.6%, 23.8%, and 0%, respectively ( P  = 0.007). Revision rates for C7, T1, and T2 LIV were 25.0%, 11.9%, and 0%, respectively ( P  = 0.013). No difference was noted in average time to revision/failure between C7 (39.68 months) and T1 (29.85 months) LIV cohorts. No differences in baseline, 3-month, and 12-month postoperative PRO measures were noted in the C7 and T1 LIV cohort when compared to the T2 LIV cohort. Conclusion: The findings in this study indicate that PCF LIV selection may play a significant role in the development of mechanical complications and need for revision surgery. T2 LIV selection demonstrated a significantly lower rate of mechanical failure and revision surgery. Postoperative PROs up to 36 months are needed to evaluate effect of LIV selection on PROs. Level of Evidence: 3 Abstract : A retrospective spine registry study illustrating a significant effect of cervicothoracic posterior cervical fusion lowest instrumented vertebra selection (C7 vs. T1 vs. T2) on the development of mechanical complication and revision surgery.